Optimasi Hydroxypropyl Methylcellulose dan Chitosan pada Tablet Floating-Mucoadhesive Diltiazem Hidroklorida Menggunakan Desain Faktorial - Irsalina Triastutik; Lusia Oktora Ruma Kumala Sari; Lina Winarti (Pustaka Kesehatan, 2020)
Diltiazem HCl is one of the drugs used for hypertension treatment. It requires frequent dosing, which is why diltiazem HCl needs to be formulated into preparations using a controlled release drug delivery system. The combination of floating and the mucoadhesive system is expected to increase the stomach's retention of the dosage form. This study aimed to determine the optimum composition of hydroxypropyl methylcellulose (HPMC K100M) and chitosan for floating mucoadhesive diltiazem HCl tablet. Tablets that have been prepared were evaluated for the tablet's physical characterization, powder flowability test, dissolution test, floating ability, and mucoadhesive test. Tablets were optimized using a factorial design, and the data were analyzed using design expert 11.0.0. The results showed that the optimum formula for polymer combination in diltiazem HCl tablet was 175 mg for HPMC K100M and 50 mg for chitosan. The combination of polymers with this amount can produce a floating lag time of 45,333 seconds, floating duration time >12 hours, and the strength of mucoadhesive is 81,633 grams.